Burnout Level in Pencak Silat Extracurricular Students of SMK Negeri 7 Palembang During the Covid-19 Pandemic - Ismail, Ismail; Junaidi, Ilham Arvan; Akhbar, M Taheri (Universitas Negeri Padang, 2024)
Background and Aim. During the COVID-19 pandemic, students involved in sports extracurricular activities, including pencak silat, faced various psychological challenges such as burnout. This study aims to determine the level of burnout among pencak silat extracurricular students at SMK Negeri 7 Palembang.Method. This study uses a quantitative descriptive method. Data were collected through questionnaires and observations involving students participating in pencak silat extracurricular activities.Results. The results show that internal factors contributing to burnout include emotional exhaustion, depersonalization, and decreased personal achievement. From 17 indicators, responses varied across categories ranging from very good to very poor. External factors such as workload, social support, and role conflict also influenced burnout levels. Based on 38 questionnaire items distributed to 15 students, the responses indicated varying perceptions, with the highest proportion categorized as very good (38.10%). Overall, the burnout level falls into the high category, with a score of 11986.66 (119.86%) within the 80–100 interval, indicating a very high level.Conclusion. The findings indicate that pencak silat extracurricular students experienced a high level of burnout during the pandemic, influenced by both internal and external factors.